2021
DOI: 10.1101/2021.05.26.445787
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 Nsp14 activates NF-κB signaling and induces IL-8 upregulation

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection leads to NF-κB activation and induction of pro-inflammatory cytokines, though the underlying mechanism for this activation is not fully understood. Our results reveal that the SARS-CoV-2 Nsp14 protein contributes to the viral activation of NF-κB signaling. Nsp14 caused the nuclear translocation of NF-κB p65. Nsp14 induced the upregulation of IL-6 and IL-8, which also occurred in SARS-CoV-2 infected cells. IL-8 upregulation was further confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 71 publications
3
42
0
Order By: Relevance
“…In our analysis of the promoters of early upregulated genes, we also detected enrichment for binding sites of transcription factors involved in the interferon response. In support of our findings, recent reports showed that Nsp14 reduces the expression of INFb and ISG luciferase reporters (Yuen et al, 2020), as well as the expression of proteins involved in the NFkB pathway (Hsu et al, 2021;Li et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In our analysis of the promoters of early upregulated genes, we also detected enrichment for binding sites of transcription factors involved in the interferon response. In support of our findings, recent reports showed that Nsp14 reduces the expression of INFb and ISG luciferase reporters (Yuen et al, 2020), as well as the expression of proteins involved in the NFkB pathway (Hsu et al, 2021;Li et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…Early after transfection with the Nsp14 expression vector, we detected increased CXCL8 expression, which encodes IL8. IL8 is elevated in plasma of COVID-19 patients (Blanco-Melo et al, 2020;Hariharan et al, 2021;Li et al, 2021) and is a marker of acute severe lung distress (Adcock et al, 2015), an inflammatory condition that can lead to severe complications or death. Use of a reporter assay showed that Nsp14 influences transcription of CXCL8.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations